Studying Of Physico-Chemical Properties Of 5-(2-,3-Fluorophenyl)-4-((Aryl-, Geteryl) Yliden) Amino-1,2,4-Triazole-3-Thiols And Any Of Their Retrievalproducts - Bihdan, O. A.; Parchenko, V. V.; Zazharskyi, V.; Fotina, T.; Davydenko, P.; Бігдан, Олексій Антонович; Парченко, Володимир Володимирович (My University, 2019)
The need for highly effective and low-toxic drugs is constantly increasing in the modern world. Therefore, the creation of new original molecules, which can turn into effective bioactive compounds, and then into drugs, is a topical issue of the modern pharmaceutical and medical industries. The purpose of the work is to study the physico-chemical properties of new 5-(2-,3-fluorophenyl)-4-((aryl,heteryl)ylidenes)amino-1,2,4-triazole-3-thiols and some products of their reduction. As the starting compounds, we used 5-(2-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol and 5- (3-fluorophenyl) -4-amino-1,2,4 -triazole-3-thiol.
Keywords: 2-, 3-fluorophenyl derivative 4-amino-1,2,4-triazole; physical and chemical properties; chemical transformations; regeneration